Education using the emo-demo method increases knowledge and attitudes of third-trimenster pregnant women on giving exclusive breast milk - Armini, Ni Wayan; Surati, Gusti Ayu; Mauliku, Juliana; Marhaeni, Gusti Ayu (Jurnal Kesehatan Ibu dan Anak, 2019)
Achieving the target of exclusive breastfeeding for babies tends to decrease from year to year. This is a threat to children's development. Various efforts have been made, but do not have sufficient leverage to improve the knowledge and attitudes of mothers. The purpose of this study was to know the effect of education with the methods emo-demo on the knowledge and attitude of pregnant women in the third trimester of exclusive breastfeeding in the health center of Denpasar. This research was a quasi-experimental research with a non-equivalent group design, carried out in Denpasar Public Health Center working area from May until October 2018. The technique was using purposive sampling with a sample size of 40 respondents in both the treatment group using the emo-demo method and control group using the conventional counseling method with Maternal and Child Health book. Statistical tests used the Wilcoxon test and the Mann Whitney test. The comparison result of knowledge between control and treatment group was -3.758; p-value: 0.000. The comparison result of attitudes between control and treatment group was -3.601; p-value: 0.000. Education using the emo-demo method was able to improve the knowledge and attitudes of third-trimester pregnant women in exclusive breastfeeding compared to education with conventional counseling according to the MCH book standards. Emo-demo method was more effective to increase knowledge and attitudes of third-trimester pregnant women in giving education about exclusive breastfeeding.